The SmartAG partner: CCAFS East Africa Quarterly Newsletter, April – June 2016 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
We are pleased to share with you our quarterly newsletter. We present key highlights from ongoing research and policy engagement from April to June 2016. In May, policy makers from Kenya’s Climate Change Directorate and Uganda’s Climate Change Department, visited CCAFS and International Livestock Research Institute (ILRI) to dialogue on tools for greenhouse gas (GHG) measurements and inventories for East Africa. Find out more about this meeting. Kenya has recently put in place a Climate Change Act, 2016 which is a comprehensive climate change law. Within the Act, a National Climate Change Council will be set up to coordinate the country’s climate change efforts. Read more about the Act. From Uganda, a platform to prioritize local climate-smart agriculture options has been launched in Mbale district. Read an update from the Policy Action for Climate Change Adaptation project. At the seventh Africa Agriculture Science Week (AASW7) held from 13 – 16 June in Kigali, Rwanda, stakeholders discussed exciting opportunities to make climate services available to farmers in Rwanda. Read key messages emerging from a side event organized by CCAFS and partners. Read highlights on recent outcomes and innovations from CCAFS partners from the CCAFS 2015 annual report. A recently released paper by ILRI scientists helps us understand small ruminant production, based on lessons from the CCAFS climate-smart villages (CSVs) of Nyando in Western Kenya. From the Lushoto CSVs in Tanzania, CCAFS Working Paper 173 compiles lessons from the Farms of the Future approach on enhancing farmers adaptive capacity through learning journeys.